TIME-RESOLVED NEUTRON DIFFRACTION STUDIES WITH EMPHASIS ON WATER ICES AND GAS HYDRATES - Kuhs W.F.; Hansen T.C. (My University, 2006)
This chapter deals with applications of neutron diffraction to the understanding of transformation processes in geomaterials with a time-resolution from seconds to several days. The choice of neutrons rather than X-rays for such time-resolved studies is due to their specific advantages like e.g., the sensitivity to light elements, the detection of volume rather than surface phenomena or the low absorption in case of bulky sample environments. General features of diffractometers suitable for time-resolved studies are discussed and the high-flux diffractometer D20 at ILL is presented in some detail. Time-resolved processes usually are studied at nonambient pressures and temperatures. The necessary sample environment needs to be provided and matched to the diffractometer set-up. Processes in water ices and gas hydrates are taken as examples and will be used to demonstrate the capabilities and limitations of the method.